Myokine Regulation as Marker of Sarcopenia in Elderly - I Gusti Putu Suka Aryana; Anak Agung Ayu Ratih Hapsari; Raden Ayu Tuty Kuswardhani (Cell and BioPharmaceutical Institute, 2018)
The elderly population will increase as well as increasing life expectancy. Health problems in elderly will be more complex and need a comprehensive management. One of the problems that arise from the aging process is sarcopenia. Sarcopenia is a decreasing in muscle mass and muscle strength or muscle function caused by multifactorial not only due to aging process, but also nutrition, immobilization, genetics and others risk factors. Muscle is an endogen organ that produces various proteins that can affect the health system. This protein is referred to as myokine. Myokine is anti-inflammation cytokine and peptide produced by striated muscles. Physical activity results in myokine secretion that can reduce inflammation due to a sedentary lifestyle. Inflammation can lead to worsening sarcopenia and fat accumulation in striated muscles, thus reducing muscle mass, muscle strength and causing physical inactivity. The most of this type myokine have antiinflammation effect have work as autocrine, paracrine and endocrine. Chronic inflammation is a contributor that plays a role in the pathophysiology of various diseases including sarcopenia, it will protected by myokine. Myokine can affect the metabolism of glucose, fatty acids, angiogenesis, myogenesis, neurogenesis, and can explain the relationship between muscle, liver, fat, tissue and brain. Some knewn myokines include interleukin (IL)-6, IL-8, IL-5, brain-derived neurotrophic factor (BDNF), fibroblast growth factor 21 (FGF-21), leukemia Inhibitory factor (LIF), irisin and secreted protein acidic and rich in cysteine (SPARC). Physical exercise can induce myokine secretion from striated muscle to circulation. Through these mechanisms, myokine is expected to improve metabolism of glucose, fat and protein muscle, liver, fat, tissue, brain and reduce the incidence some comorbidity especially sarcopenia. Finally, it's will be decreasing of disability, morbidity and mortality rate in elderly.Keywords: myokine, sarcopenia, elderly